2019
DOI: 10.4103/jqsh.jqsh_24_18
|View full text |Cite
|
Sign up to set email alerts
|

Radiograph Reject Analysis in a Large Tertiary Care Hospital in Riyadh, Saudi Arabia

Abstract: Background: Analysis of rejected radiographs is an important quality indicator of any radiology department. At King Abdulaziz Medical City (KAMC), about 185,000 radiographs are performed annually. Methods: The rejected radiographs over a period of 5 years were analyzed using a dedicated electronic rejection system. The rejection is performed by a certified radiologist and communicated electronically to the concerned technologist. Results: A total of 455 rejected radiographs were reviewed and analyzed. Of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…6,7 For a diagnostic radiology department to be able to provide images of high quality with the minimum exposure of patients and staff to the radiation, a program of quality assurance needs to be set and accomplished. 8,9 The reasons for the rejection of images correspond with technical alternated advances. The most common reason to reject images in conventional filmscreen radiology was reported to be exposure errors (that is, too much or too little exposure).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 For a diagnostic radiology department to be able to provide images of high quality with the minimum exposure of patients and staff to the radiation, a program of quality assurance needs to be set and accomplished. 8,9 The reasons for the rejection of images correspond with technical alternated advances. The most common reason to reject images in conventional filmscreen radiology was reported to be exposure errors (that is, too much or too little exposure).…”
Section: Introductionmentioning
confidence: 99%
“…Patients might undergo repeated X-ray examinations after their initial X-ray radiographs are rejected due to different reasons such as poor image quality, artifact, anatomical cutoff, patient motion, and equipment malfunction [ 3 ]. Rejected radiographs that are repeated, may lead to extra radiation dose to the patient; reduction in the lifetime of the X-ray machines, which added expenses on the health care system; and long waiting list [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, rejected images lower the adequacy of the department and patient gratification, which, as a result, will raise departmental charges. 6 World Health Organization recommends a rejection rate of 5%; meanwhile, the Committee on Quality Assurance of the Conference of Radiographic Control Program Directorate 7 suggests a rejection rate of 10%. Several studies reported a rejection rate ranging from 2.1% to 33%, and the reasons for these differences include positioning errors, motion errors, or miscellaneous errors.…”
mentioning
confidence: 99%